Economic Impact of Four Cylinder Pedal Pump in a Selected Area of Bangladesh - Alam, QM; Islam, R; Baset, MA (Journal of Agriculture & Rural Development, 2008)
The study was conducted in Rajshai Barind area to know the short and long term impact of for cylinder manual (Pedal) Pump developed by Bangladesh Agricultural Research Institute. The Pump was dominated by small farmers who cultivated vegetables in homestead fallow land. Simple cost and return analysis indicated that the pump was profitable in the short-run. It was found that in both private and social point of view the pump was profitable and acceptable in the short run as well as in the long run. The command area of the pump was 0.20 ha. The pump was found underutilized. For full utilization of the pump, its operation should be extended to the main field where water source is available. Nevertheless, the pump is a substitute to modern irrigation system. Key words: Pedal pump, irrigation, vegetable production.